Rotavirus, PCV And HPV Immunization Coverage In Bima City In 2024 - Dian Mariza Rizkiah A; Susanti Susanti; Nurbaiti Nurbaiti (Jurnal EduHealth, 2025)
Immunization is an effective way to prevent disease transmission and reduce morbidity and mortality rates in infants and toddlers. Additional immunizations recommended by IDAI are pneumococcal vaccine (PCV), rotavirus, influenza, HPV, varicella, Japanese Encephalitis (JE), Hepatitis A and Typhoid (IDAI, 2020). The aim of this study is to determine the coverage of additional immunizations for Rotavirus, PCV and HPV in Bima City in 2024. This research method is quantitative descriptive with a secondary data analysis approach to describe the coverage of Rotavirus, PCV and HPV immunization in Bima City The population in this study was all children who received Rotavirus, PCV and HPV immunization during 2024, with the entire population being sampled. Based on the research results, it was found that Rotavirus immunization coverage in 2024 was 82.1%, HPV immunization coverage was 81.5%, and for HPV immunization coverage in 2024 was 72.6%